Analisis Implementasi Teknik Wawancara Film Dear Zindagi - Sofiyah, Zulaehatus (Journal of Islamic Education Counseling, 2021)
Prospective counsellors rarely had been getting a complete picture of the influence and manner of interview techniques in a real case. So, this study aims to show an overview of how interview techniques are conducted in the movie of Dear Zindagi by analyzing the theory of interviews that exist. Research method used qualitative method with trianggulasi data taken from documentation of movie and interview technique theory. The results showed that the interview techniques practiced in the film Dear Zindagi are in accordance with the rules of counseling, especially in the interview techniques that make the counsellor feel comfortable, safe and calm to tell the counsellor